Mechanical characterization of polyvinil butyral from static and modal tests on laminated glass beams. (15th July 2019) - López-Aenlle, M.; Noriega, A.; Pelayo, F.
Abstract: Polyvinyl butyral (PVB) is the polymeric interlayer material most used in laminated glass elements. As other used interlayers, the PVB mechanical behavior is viscoelastic. Therefore, its mechanical characterization can be carried out by static (creep and relaxation) or dynamic tests in a dynamic mechanical analyser (DMA). However, the PVB layers constrained in laminated glass elements are subject to high temperature and pressure conditions in an autoclave during the manufacturing process, which can affect to the mechanical properties of the interlayer. In this paper, the mechanical properties of PVB constrained in laminated glass beams have been determined by static and dynamic tests on laminated glass beams with different boundary conditions and at different temperatures. The estimated curves are compared with those obtained by testing free PVB specimens in a DMA.